First Record of Argulus japonicus (Crustacea: Branchiura) on Cyprinus carpio in Nepal, with Additional Notes on Morphology and Prevalence of A. Japonicus and Its Treatment (Nepalese Veterinary Journal, 2017)
The present study recorded the parasite Argulus japonicus (Crustacea: Branchiura) as the first discovery in Nepal. The description was based on using 11 males (4.12 mm average TL) and 5 females (4.18 mm average TL) of Argulus japonicus which were collected from Godawari fish farm, Lalitpur. Biological behavior of one summer old common carp (Cyprinus carpio) infected with Argulus japonicuswere sluggish movement, jumping and poor growth grown in earthen pond in winter at water temperature 15.5 ºC and pH 7.4. Heavily infected fishes showed brown-grey to reddish points throughout their body surface, especially on the caudal fins and on the body portion. Prevalence rate of this parasite was 80% in infected common carp fish with an average weight 261.80±85.12 g and length 22.9±4.9 cm. Argulus mean intensity count was averaged 10.2 per infected fish with relatively high infestation in body surface (2.8±3.9) followed by caudal fin (1.8±4.5) and dorsal fin (1.1±1.5). Prevalence rate of this parasite in treated common carp reduced by 95% and Argulids assembled in several regions of the fish was in average 0.1/treated fish by feeding Duroclean treated feed. Duroclean, an aquaculture drug was found effective to control this parasite. The effective dose of the drug was 0.3 g per kg fish feed and fed for 3 days consecutively with one day off and then again for 2 days.